Particle swarm optimization technique for optimal economic load dispatch / Muhammad Hilmi Nordin - Nordin, Muhammad Hilmi (2014)
In the operation and planning of a power system, Economic Load Dispatch is a crucial task to be performed which decided the generation schedule of generating units with the objective of minimizing the total fuel cost while maintaining the operational constraints. In this proposal paper, an optimization technique called the Particle Swarm Optimization (PSO) technique that is a meta-heuristic optimization technique, are proposed to solve the economic load dispatch problem. PSO is an algorithm that is modeled on swarm intelligence that finds a solution to an optimization problem in a search space, or model, and predicts social behavior in the presence of objectives. The application of PSO in economic load dispatch problem can be considered as one of the most complex optimization problem